Contrast Sensitivity of Thyroid Associated Ophthalmopathy Patients without Obvious Optic Neuropathy - Ümit Beden; Sümeyra Kaya; Volkan Yeter; Dilek Erkan (The Scientific World Journal)
Purpose. To compare the contrast sensitivity levels of thyroid associated ophthalmopathy (TAO) patients without obvious optic neuropathy with those of healthy people. Methods. Forty eyes of 20 TAO patients without dysthyroid optic neuropathy and 40 eyes of 20 healthy subjects were evaluated in this prospective case-controlled study. The contrast sensitivity functions (CSFs) of all subjects were measured by the functional acuity contrast test (FACT) in five frequencies which were 1,5 cpd (A), 3 cpd (B), 6 cpd (C), 12 cpd (D), and 18 cpd (E). Results were compared for both groups, and a correlation of CSF with Hertel and clinical activity scores was assessed. Results. There was no statistically significant difference between TAO patients and control groups for age and sex. TAO patients had lower levels than the control group in all the frequencies of CSFs (P<0.05) and the difference in contrast sensitivity functions between the groups seems to be more significant in higher frequencies (B, C, D, and E) (P<0.001). Conclusions. TAO patients without DON can have contrast sensitivity loss and this would probably imply subtle optic nerve dysfunction in early disease phase.